Challenges and Strategies in Strengthening the Implementation of the Independent Curriculum in Islamic Religious Education Learning - Yunia Dwi Latifah (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
This article is a literature review that aims to identify the challenges and strategies for strengthening the implementation of The Independent curriculum in Islamic Religious Education (PAI) learning in high school. By integrating a wide range of literature, the study explores issues such as teacher readiness, technology access, and curriculum adaptation, as well as offering strategies such as continuous training and contextual learning approaches. The findings suggest that key challenges include teachers ' lack of digital competence, infrastructure inequality, and resistance to changes in teaching methods. The proposed strategies include strengthening technology literacy, developing adaptive PAI modules, and collaboration among stakeholders to support effective implementation.